Testing a new surgical instrument to obtain bovine hoof biopsy samples - Mendes, Heloisa M.F.; Rocha Júnior, Sérgio S.; Paz, Cahuê F.R.; Valadares, Rodrigo C.; Ribeiro, Rodrigo M.; Azevedo, David S.D.; Vasconcelos, Anilton C.; Faleiros, Rafael R. (Pesquisa Veterinária Brasileira, 2018)
The histological and molecular analysis of biopsy samples are fundamental steps for the understanding of physiopathology, diagnosis and prognosis of the diseases. However, harvest of tissue biopsies from hoof lamellar tissue is a procedure with limitations due to lack of effective surgical instruments and techniques. The aim of the current study is to develop and test in vivo a surgical instrument with the specific purpose of harvesting lamellar tissue in cattle. A prototype called Falcão-Faleiros’ lamellotome (INPIBR102013018765-8) was designed, produced and tested. After sedation, five adult cattle were restrained in lateral recumbency and locally anesthetized in two digits. The stratum corneum was worn down using a rotary tool coupled to a 3/8” high-speed cutter until the soft tissue proximity was reached. Next, the inner edge of the worn area was bounded with a scalpel. The lamellotome was introduced to obtain and hold the sample. The histological specimens of 16mm length by 6mm depth were stained with HE, PAS, Masson’s thricome and Shorr. The structures of interest were differentiated in the histological analysis without technical artifacts and a mean number of 85 epidermal laminae per sample were counted. No relevant lameness or wound complication were seen following the procedure. In conclusion the technique using the lamellotme was effective in obtaining lamellar tissue biopsy samples without causing clinical harm in cattle. The procedure showed potential to be used in clinical research or even as a supplementary diagnosis method for routine bovine podiatry. RESUMO: A avaliação das propriedades histológicas e da expressão de genes e proteínas em biópsias tem sido determinante para o entendimento da fisiopatologia, o diagnóstico e o prognóstico das enfermidades. Entretanto, a obtenção de biópsias do casco é um procedimento com limitações devido à ausência de técnicas e instrumentos específicos. O objetivo foi desenvolver e testar, na espécie bovina, um instrumento cirúrgico especificamente desenvolvido para realização de biópsias de casco nominado lamelótomo de Falcão-Faleiros (INPI, BR102013018765-8). Utilizaram-se cinco bovinos adultos que foram sedados, contidos em decúbito lateral e tiveram dois dígitos anestesiados. Em seguida, uma serra circular acoplada a uma microretífica foi usada para o desgaste do estrato córneo na parede dorsal até próximo do estrato lamelar. Após incisões retilíneas delimitando a borda interna da área desgastada, utilizou-se o lamelótomo para obtenção da amostra. Os fragmentos de 16mm de comprimento e 6mm de profundidade foram fixados em formalina e processados para histologia com colorações HE, PAS, Shorr e tricrômico de Masson. Nenhum dos animais apresentou claudicação ou complicação relevantes no período pós-opertório. As amostras foram consideradas adequadas quanto à integridade das lâminas e à preservação de sua arquitetura. Obtiveram-se média de 85 lâminas epidérmicas viáveis por biópsia. Conclui-se que o lamelótomo de Falcão-Faleiros é apropriado e seguro para a obtenção de biópsias de casco em bovinos, se mostrando promissor para uso em estudos clínicos e na rotina de diagnóstico de problemas podais em bovinos.